Pinelliae rhizoma alleviated acute lung injury induced by lipopolysaccharide via suppressing endoplasmic reticulum stress-mediated NLRP3 inflammasome - Wang, Ning-ning; Zhang, Xian-xie; Shen, Pan; Huang, Cong-shu; Deng, Hui-fang; Zhou, Lei; Yue, Lan-xin; Shen, Bao-ying; Zhou, Wei; Gao, Yue (Frontiers in Pharmacology, 2022)
Pinelliae Rhizoma (PR), one kind of commonly used Chinese herbs, is generally prescribed to treat various respiratory diseases, including acute lung injury (ALI). However, the accurate bioactive ingredients of PR and the underlying pharmacological mechanism have both not been fully elucidated. Therefore, this study aimed to identify the bioactive ingredients that could alleviate lipopolysaccharide (LPS)-induced ALI and explore the possible mechanism involved. Our results confirmed that LPS infection indeed caused acute inflammatory damage in mice lung, accompanying with the enhancement of IL-1β contents and the activation of the NLRP3 inflammasome in lung tissue and macrophagocyte, all of which were remarkably ameliorated by PR treatment. Mechanistically, LPS was found to trigger endoplasmic reticulum (ER) stress and downstream cellular calcium ions (Ca2+) release via activating Bip/ATF4/CHOP signaling pathway. Like PR, 4-PBA (a specific inhibitor of ER stress) not only obviously reversed Bip/ATF4/CHOP-mediated ER stress, but also significantly attenuated LPS-induced activation of the NLRP3 inflammasome. Furthermore, the bioactive ingredients of PR, which generated the anti-inflammatory effects, were screened by metabolomics and network pharmacology. In vitro experiments showed that chrysin, dihydrocapsaicin (DHC) and 7,8-dihydroxyflavone (7,8-DHF) notably suppressed LPS-induced ER stress and following NLRP3 inflammasome activation. In conclusion, our findings suggested that PR alleviated LPS-induced ALI by inhibiting ER stress-mediated NLRP3 inflammasome activation, which is mainly relevant with these three bioactive ingredients. This study provided a theoretical basis for the clinical application of PR to treat ALI, and these bioactive ingredients of PR would be promising therapeutic drugs for the treatment of ALI.